United Arab Emirates : Selected Issues. (IMF Staff Country Reports; Country Report, 2013)
This Selected Issues paper on the United Arab Emirates highlights the macroprudential policies. The fixed exchange rate and persistent structural liquidity surpluses in upswings add to the difficulties in managing aggregate demand contain credit expansion. The exchange rate peg and the open capital account allow limited room to deviate from the U.S. interest rates. Monetary policy is further constrained by limited liquidity management capabilities, as liquidity forecasting is in its infancy, and central banks liquidity management relies primarily on reserve requirements and standing facilities for liquidity absorption. The lack of a local currency fixed-income market raises the prominence of real estate as an asset class for investment and the exposure of the banking system to the real estate sector.